Combined testing of copeptin and high-sensitivity cardiac troponin T at presentation in comparison to other algorithms for rapid rule-out of acute myocardial infarction - Müller-Hennessen, Matthias; Giannitsis, Evangelos; Vafaie, Mehrshad; Biener, Moritz; Katus, Hugo (International journal of cardiology, 2019)
Background We aimed to directly compare the diagnostic and prognostic performance of a dual maker strategy (DMS) with combined testing of copeptin and high-sensitivity (hs) cardiac troponin T (cTnT) it time of presentation with other algorithms for rapid rule-out of acute myocardial infarction (AMI). Methods 922 patients presenting to the emergency department with suspected AMI and available baseline copeptin measurements qualified for the present TRAPID-AMI substudy. Diagnostic measures using the DMS (copeptin <10, <14 or<20pmol/L and hs-cTnT≤14ng/L), the 1h-algorithm (hs-cTnT<12ng/L and change <3ng/L at 1h), as well as the hs-cTnT limit-of-blank (LoB, <3ng/L) and -detection (LoD, <5ng/L) were compared. Outcomes were assessed as combined end-points of death and myocardial re-infarction. Results True-negative rule-out using the DMS could be achieved in 50.9%-62.3% of all patients compared to 35.0%, 45.3% and 64.5% using LoB, LoD or the 1h-algorithm, respectively. The DMS showed NPVs of 98.1%-98.3% compared to 99.2% for the 1h-algorithm, 99.4% for the LoB and 99.3% for the LoD. Sensitivities were 93.5%-94.8%, as well as 96.8%, 98.7% and 98.1%, respectively. Addition of clinical low-risk criteria such as a HEART-score≤3 to the DMS resulted in NPVs and sensitivities of 100% with a true-negative rule-out to 33.8%-41.6%. Rates of the combined end-point of death/MI within 30days ranged between 0.2% and 0.3% for all fast-rule-out protocols. Conclusion Depending on the applied copeptin cut-off and addition of clinical low-risk criteria, the DMS might be an alternative to the hs-cTn-only-based algorithms for rapid AMI rule-out with comparable diagnostic measures and outcomes.
Available online 26 October 2018
Gesehen am 19.02.2019